Stress evaluation method

JP7634260B2Active Publication Date: 2025-02-21KOBE UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021064037
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-05
Publication Date
2025-02-21
Estimated Expiration
2041-04-05

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、樹脂-樹脂間の残留応力を評価可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634260000002
    Figure 0007634260000002
  • Figure 0007634260000003
    Figure 0007634260000003
  • Figure 0007634260000004
    Figure 0007634260000004
Patent Text Reader

Abstract

To provide a new evaluation method capable of evaluating a residual stress between pieces of resin.SOLUTION: A stress evaluation method includes (1) a first process for applying incidence X rays from one surface side of a sample in a laminate shape having a first layer containing a crystalline polymer, and a second layer that is composed of a resin material and is provided in contact with one surface of the first layer, and for detecting diffraction X rays emitted from the other surface side of the sample, and (2) a second process for obtaining a minute strain ε in a gap between lattice surfaces of a crystal lattice in a crystalline polymer on the basis of diffraction X rays, and evaluates stress σ between the first layer and the second layer on the basis of the minute strain ε.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stress evaluation method, and more particularly to a stress evaluation method using an X-ray diffraction method. [Background technology]

[0002] In composite materials in which different materials are bonded, it is important academically and industrially to appropriately evaluate the residual stress at the interface between the different materials. For example, evaluation of the residual stress at the interface between a substrate and an adhesive applied to the substrate can provide important information on the adhesion mechanism and guidelines for improving the adhesive.

[0003] X-ray stress measurement is a conventional technique for measuring residual stress at the interface between different materials. In X-ray stress measurement, the angle ψ between the normal to the sample surface and the normal to the lattice plane where the X-rays are diffracted is typically changed to measure the lattice strain of the crystal, and the residual stress is evaluated from the strain. By using this method, the residual stress can be evaluated nondestructively and easily.

[0004] As background art relating to measurement of residual stress by X-ray stress measurement method, the following Non-Patent Documents 1 and 2 can be mentioned, for example. In Non-Patent Document 1, it is reported that the stress at the interface was evaluated by irradiating X-rays on a sample in which an epoxy adhesive was applied to the surface of an aluminum substrate and hardened. 2 It describes how to calculate residual stress using the ψ method. In Non-Patent Document 2, a sample in which a polyimide film was formed on the surface of an aluminum substrate was irradiated with X-rays, and the sin 2 It is described that residual stress was calculated using the ψ method. Non-Patent Document 3 is a review of residual stress measurement methods. In item 3 of this document, the measurement of residual stress by X-ray diffraction method is described. This document also describes other residual stress measurement methods. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] "X-ray evaluation of adhesion and fatigue properties in composite materials" Materials Life 12[2]67-70 [Non-Patent Document 2] "X-ray evaluation of residual stress at polyimide / aluminum interface" Proceedings of the Academic Lectures of the Society of Materials Science, Japan, 49, 307-308 [Non-Patent Document 3] "Method of measuring residual stress" Journal of the Adhesion Society of Japan, Vol. 39, No. 1 (2003) 24-29 Summary of the Invention [Problem to be solved by the invention]

[0006] In Non-Patent Documents 1 to 3, the residual stress between metal and resin materials is evaluated by X-ray stress measurement.

[0007] On the other hand, in recent years, in the mobility field, for example in aircraft, resin materials have been used as an alternative to metal materials, and research is being conducted into bonding resin materials together. For this reason, it is important to appropriately evaluate the residual stress between resins when two different resin materials are bonded together in order to expand the use of polymer materials and ensure product reliability.

[0008] The present inventors have now carried out investigations with the aim of providing a new evaluation method capable of evaluating the residual stress between resins. [Means for solving the problem]

[0009] As a result of their investigations, the inventors have completed the invention provided below.

[0010] According to the present invention, a first step of irradiating an incident X-ray onto one surface of a laminated sample, the sample comprising a first layer containing a crystalline polymer and a second layer made of a resin material and provided in contact with one surface of the first layer, and detecting diffracted X-rays emitted from the other surface of the sample; a second step of determining a microstrain ε of the lattice spacing of the crystal lattice of the crystalline polymer based on the diffracted X-rays; and evaluating a stress between the first layer and the second layer based on the small strain ε. is provided. Effect of the Invention

[0011] According to the present invention, it is possible to evaluate the residual stress between resins. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram for explaining the stress evaluation method, particularly the first step. [Diagram 2] FIG. 13 is a supplementary diagram for explaining the sin2ψ method. [Diagram 3] Fig. 3A shows the shift of the diffraction peak associated with the microstrain of the crystals of isotactic polypropylene with the change in sin2ψ in Example 1. Fig. 3B shows a graph plotting the microstrain ε on the vertical axis and sin2ψ on the vertical axis in Example 1. [Figure 4] Fig. 4A shows the shift ε of the diffraction peak associated with the microstrain of the crystals of isotactic polypropylene with the change in sin2ψ in Example 2. Fig. 4B shows a graph plotting the microstrain ε on the vertical axis and sin2ψ on the vertical axis in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to the actual objects.

[0014] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass". In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate."

[0015] <Stress evaluation method> (1st step) FIG. 1 is a diagram for explaining the stress evaluation method of the present embodiment, particularly the first step. In the first step, incident X-rays are irradiated from one surface of a laminated sample having a first layer containing a crystalline polymer and a second layer made of a resin material and provided in contact with one surface of the first layer, and diffracted X-rays emitted from the other surface of the sample are detected by using an appropriate means or device (not shown). The incident X-rays are usually incident on the second layer side of the laminated sample.

[0016] In the stress evaluation methods described in Non-Patent Documents 1 to 3, the first layer is aluminum (metal material), and the diffracted X-rays are detected on one surface side of the sample (the surface on which the incident X-rays are incident). At least in these respects, the stress evaluation method of this embodiment differs from conventional stress evaluation methods. Another way of looking at this is that in this embodiment, by using a first layer that is X-ray transparent, diffracted X-rays can be detected on the surface opposite to the surface on which the incident X-rays are incident.

[0017] The incident X-rays may be incident perpendicularly or non-perpendicularly to the surface of the first layer facing the second layer. To detect stress parallel to the interface between the first and second layers, the lattice plane of the crystal of the crystalline polymer must be tilted by the Bragg angle with respect to the incident X-rays. In this case, the incident X-rays are usually incident non-perpendicularly to the surface of the first layer facing the second layer. In other words, the incident X-rays are preferably incident at an angle that is the Bragg angle with respect to the lattice plane of the crystal of the crystalline polymer contained in the first layer. In other words, the incident X-rays are preferably incident on the sample at an angle at which diffraction occurs according to the Bragg equation (described later).

[0018] In the third step described below, sin 2 To apply the ψ method, in the first step, it is preferable that incident X-rays are incident on crystals of two or more different orientations in the first layer. Specifically, the first layer may be polycrystalline, containing microcrystals of various orientations (two or more different orientations), where sin 2 To apply the ψ method, for example, it is preferable to obtain diffracted X-rays by irradiating incident X-rays (at an angle that satisfies the Bragg equation) on microcrystals whose ψ in Fig. 2A is 0°, 15°, 30°, 45°, and 60°. In other words, it is preferable to perform incidence of X-rays and detection of diffracted X-rays at a plurality of different ψ. In FIG. 2A, ψ is the angle between the sample surface and the lattice normal. The "sample surface" refers to the surface of the first layer on the side where the second layer is provided. Also, θ is the Bragg angle. For reference, FIG. 2B shows a special case of FIG. 2A where ψ is 0°. Incidentally, in conventional X-ray stress measurement methods as described in Non-Patent Documents 1 to 3, ψ is usually taken as the angle between the "normal" to the sample surface and the normal to the lattice surface. That is, the conventional X-ray stress measurement method and the X-ray stress measurement method of this embodiment take ψ differently. This is because the conventional X-ray stress measurement method is a "reflection method" in which diffracted X-rays are detected on the surface on the side where the incident X-rays are incident, whereas the X-ray stress measurement method of this embodiment is a "transmission method" in which diffracted X-rays are detected on the surface opposite to the side where the incident X-rays are incident.

[0019] In order to make the incident X-rays incident on crystals of two or more orientations, the first step may be performed multiple times with different angles of incidence of the incident X-rays on the sample, or the angle of incidence of the incident X-rays on the sample may be continuously changed to continuously detect diffracted X-rays. The "angle of incidence of the incident X-rays on the sample" refers to the angle between the surface of the first layer that is provided with the second layer and the incident X-rays. Regarding the first layer, there are cases where the entire layer is a single crystal, and cases where multiple crystal domains exist in the sample. In the latter case, the crystal planes in the multiple crystal domains face different directions. Therefore, by performing the first step multiple times with different angles of incidence of the incident X-rays on the sample, it is possible to increase the number of crystal domains from which diffracted X-rays are obtained, and therefore the amount of data. As a result, for example, the reliability of the obtained values ​​of ε and σ can be improved.

[0020] The first layer may be made of any material as long as it contains a crystalline polymer and the lattice spacing of the crystal lattice of the crystalline polymer can be determined through X-ray diffraction. Examples of crystalline polymers include crystalline polyolefins, crystalline polyesters, crystalline polyamides, crystalline polyethers, crystalline polyurethanes, crystalline polycarbonates, crystalline polyimides, crystalline polystyrenes, and crystalline celluloses. Of course, crystalline polymers are not limited to these. In order to calculate stress in the third step, crystalline polymers whose Poisson's ratio and elastic modulus are known or can be measured with high accuracy are preferred. In particular, crystalline polymers whose crystalline elastic modulus in the direction perpendicular to the molecular chain axis is known are preferably used. Particularly preferred crystalline polymers include isotactic polypropylene and syndiotactic polypropylene.

[0021] Just to be clear, "all" of the materials constituting the first layer do not necessarily have to be crystalline polymers. As long as a diffraction X-ray profile can be obtained, the first layer may contain one or more of crystalline polymers in an amorphous state, non-crystalline polymers, organic or inorganic filler particles, etc., in addition to crystals of the crystalline polymer. In other words, the first layer can be a composite material that contains at least a crystalline polymer and further contains one or more of non-crystalline polymers, organic or inorganic filler particles, etc.

[0022] As long as the microstrain ε can be obtained in the second step, the thickness of the first layer is not particularly limited. However, in order to suppress deformation (such as curling) of the first layer due to stress between the first layer and the second layer, it is preferable that the first layer is relatively thick. Specifically, the thickness of the first layer is preferably 0.5 mm or more, more preferably 0.7 mm or more. There is no particular upper limit to the thickness of the first layer, but it is, for example, 10 mm or less. Incidentally, the thickness of the second layer may be appropriately set depending on the material to be evaluated. As long as the incident X-rays are sufficiently transmitted and reach the first layer, the thickness of the second layer is not limited. Typically, the thickness of the second layer is, for example, 1000 μm or less, preferably 500 μm or less, more preferably 200 μm or less. In addition, the thickness of the second layer is, for example, 1 μm or more, preferably 5 μm or more, and more preferably 10 μm or more.

[0023] The surface of the first layer facing the second layer may or may not be surface-treated in terms of adhesion to the second layer, etc. When the surface treatment is performed, the method is not particularly limited, and various surface treatments known in the fields of adhesion and lamination between different materials, such as oxygen plasma treatment and corona discharge treatment, can be applied. It is also possible to explore the change in stress due to surface treatment by changing the surface treatment method and conditions.

[0024] The second layer can be composed of any resin material so long as it does not unduly obstruct incident and / or diffracted X-rays. The second layer is, for example, composed of a cured product of a curable resin composition. Specifically, the second layer is composed of a cured product of an adhesive composition. By having the second layer in this configuration, it is possible to evaluate the "residual stress" caused by the curing of the curable resin composition or the adhesive composition. Examples of the curable resin composition constituting the second layer include an epoxy-based curable resin composition, a urethane-based curable resin composition, a (meth)acrylic-based curable resin composition, and a polyimide-based curable resin composition. Examples of the adhesive composition constituting the second layer include an epoxy-based adhesive composition, a urethane-based adhesive composition, a (meth)acrylic-based adhesive composition, and a polyimide-based adhesive composition. Alternatively, the second layer may be a coating film made of a coating material such as a paint composition, or may be laminated onto the first layer. In short, the second layer may be made of any material that is of interest in terms of adhesion to the first layer, residual stress, etc.

[0025] (2nd process) In the second step, the microstrain ε of the lattice spacing of the crystal lattice of the crystalline polymer is determined based on the diffracted X-rays detected in the first step. The microstrain ε can be defined as ε = (d1-d0) / d0 based on the following d1 and d0. d1: the lattice spacing of the crystal lattice of the crystalline polymer contained in the first layer, determined based on the diffracted X-rays obtained in the first step d0: The lattice spacing of the crystal lattice of the crystalline polymer contained in the first layer when the second layer does not exist

[0026] Based on the Bragg equation: 2d sinθ=λ (d is the lattice spacing of the crystal lattice, θ is the Bragg angle, and λ is the wavelength of the X-ray), d1 can be calculated from the Bragg angle θ of the diffracted X-ray detected in the first step. Also, d0 can be obtained by analyzing only the first layer by a single layer X-ray diffraction method, or a literature value may be used as d0.

[0027] (3rd step) Even up to the second step, information on the stress between the first and second layers can be obtained in the form of "microstrain ε". For example, by comparing the magnitude of ε between different samples, it is possible to qualitatively evaluate the stress without calculating a quantitative value of the stress. In other words, it is possible to evaluate the stress between the first and second layers based on the microstrain ε obtained in the second step. However, in this embodiment, it is preferable to carry out the third step described below. By carrying out the third step, the stress can be quantitatively evaluated.

[0028] In the third step, the stress between the first layer and the second layer is calculated based on the small strain ε obtained in the second step, as well as the Poisson's ratio ν and the elastic modulus E of the first layer.

[0029] In principle, it is possible to determine the stress between the first and second layers based only on the measurement results at ψ=0° shown in Figure 2B (described later). However, in order to increase accuracy and confirm the remaining uniaxial stress, it is preferable to calculate the stress as follows. In the first step, incident X-rays are irradiated onto two or more microcrystals having different orientations in the first layer, and diffracted X-rays are detected at a plurality of angles represented by ψ in FIG. 2A. That is, in the first step, two or more ψ, specifically ψ1, . . . , ψ n (n is an integer of 2 or more) In the second step, two or more microstrains ε, specifically ε1, . . . , ε2, ε3, ε4, ε5, ε6, ε7, ε8, ε9, ε10, ε11, ε12, ε13, ε14, ε15, ε16, ε17, ε18, ε19, ε20, ε21, ε22, ε n (n is an integer of 2 or greater). In the third step, the stress σ between the first layer and the second layer is calculated based on two or more small strains ε obtained in the second step. For example, (sin 2 ψ1, ε1), , (sin 2 ψ n , ε n ) is subjected to regression analysis to calculate the stress σ between the first and second layers.

[0030] The specific procedure for calculating stress is as follows: sin 2 The ψ method will now be explained. Based on previous knowledge of X-ray stress measurement, the relationship shown in the following formula (X) holds among the microstrain ε obtained in the second step, the Poisson's ratio ν of the first layer, the elastic modulus E of the first layer, the stress σ between the first and second layers, and ψ explained in Figure 2A. ε={(1+ν)σ / E}sin 2 ψ-(ν / E)σ (X) As shown in formula (X), the small strain ε is sin 2 In other words, in the first and second steps, two or more microstrains ε are calculated based on the diffracted X-rays at two or more ψ, and the microstrain ε is plotted on the vertical axis as sin 2 When ψ is plotted on the vertical axis and an approximate straight line is drawn, the slope a of the line is (1+ν)σ / E. Therefore, the stress σ can be calculated from the slope a of the line, the Poisson's ratio ν, and the elastic modulus E based on the formula a=(1+ν)σ / E. The values ​​of the Poisson's ratio ν and the elastic modulus E of the first layer may be measured by a known method, or values ​​from literature may be used. As a method for drawing an approximation curve (a specific method for regression analysis), the least squares method is preferably used, but other methods may also be used.

[0031] On the other hand, the formula (X) is ψ=0° (i.e. sin 2 In the first step, measurements are taken only at ψ=0° (by irradiating the incident X-rays on the crystallites at ψ=0°) to determine the microstrain ε, and the stress σ can be calculated by substituting the values ​​of the microstrain ε, Poisson's ratio ν, and elastic modulus E into this simplified formula. This method is based on the sin 2 Although this method is less accurate than the ψ method, it has the advantage of being simple in that the stress σ can be calculated with just one measurement at ψ=0°.

[0032] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0033] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.

[0034] <Example 1> (1) Preparation of the first layer A 1 mm thick film was produced by hot pressing using isotactic polypropylene (product number: W101) manufactured by Sumitomo Chemical Co., Ltd. One side of this film was subjected to oxygen plasma treatment (conditions: 100 W, 0.1 Torr, 10 s).

[0035] (2) Formation of the second layer An epoxy resin (jER (registered trademark) 828, manufactured by Mitsubishi Chemical Corporation), a curing agent (HN-2200, manufactured by Hitachi Chemical Co., Ltd.), and a curing accelerator (2E4MZ-CN, manufactured by Shikoku Chemical Industries Co., Ltd.) were mixed and degassed in a ratio of 100:85:1.5 (unit: parts by weight) to obtain an adhesive composition. This adhesive composition was applied onto the oxygen plasma-treated surface of the film prepared in (1), and cured at 100°C for 120 minutes, and then at 150°C for 120 minutes. This produced a laminated sample with a first layer: isotactic polypropylene and a second layer: a cured product of the epoxy adhesive. The amount of adhesive composition applied to the second layer was adjusted so that the dry thickness was 100 μm.

[0036] (3) X-ray irradiation, calculation of microstrain ε, and calculation of stress X-rays were irradiated from the second layer side of the laminated sample obtained in (2). Then, diffracted X-rays emitted from the first layer side were detected. In this case, sin 2To apply the ψ method, diffracted X-rays were obtained at ψ = 0°, 15°, 30°, 45° and 60°. The microstrain ε was calculated from the diffraction peak position from the 110 plane of the isotactic polypropylene crystal obtained from the diffracted X-rays.

[0037] (4) Results The obtained X-ray diffraction profile is shown in Figure 3A. Figure 3A also shows the X-ray diffraction profiles at ψ = 0°, 15°, 30°, 45°, and 60°. The shift of the diffraction peak due to the microstrain is also shown. The shift of the peak position depending on the value of ψ indicates the occurrence of microstrain ε in the crystal.

[0038] In addition, in Fig. 3B, the small strain ε is plotted on the vertical axis, while sin 2 A graph is shown with ψ plotted on the vertical axis. In Fig. 3B, the lattice strain decreases as ψ increases, which corresponds to the first layer being prevented from contracting in-plane and retaining tensile stress. From the gradient of the approximation line drawn based on each point, the Poisson's ratio ν (0.42) of the first layer, and the elastic modulus E (2.8 GPa) of the first layer, sin 2 The residual stress between the first and second layers, determined by the ψ method, was 8.5 MPa.

[0039] <Example 2> The same evaluation as in Example 1 was performed, except that the conditions of the oxygen plasma treatment in (1) were (150 W, 0.1 Torr, 15 s).

[0040] In Figure 4A, sin 2 The microstrain ε of the isotactic polypropylene crystals with the change in ψ and the shift in the diffraction peak with the microstrain are shown in Fig. 4B. 2 Here is a graph plotting ψ on the vertical axis. sin 2The residual stress between the first and second layers, as determined by the ψ method, was 24.1 MPa. The fact that the calculated stress was greater than that in Example 1 can be interpreted as corresponding to an increase in the adhesive strength between the first and second layers due to the change in the conditions of the oxygen plasma treatment.

[0041] <Reference: Comparison with other thermal residual stress evaluation methods> The residual stress calculated above was compared with the residual stress calculated based on other thermal residual stress evaluation methods. Specifically, the thermal residual stress was calculated based on the following formula (z), which is known as an evaluation formula for thermal residual stress using the linear thermal expansion coefficient. For reference, this formula is explained in Non-Patent Document 3.

[0042]

number

[0043] Each symbol in formula (z) has the following meaning. Tg: glass transition temperature of the second layer E: Elastic modulus of the first layer ν s : Poisson's ratio of the first layer α s : Thermal expansion coefficient of the first layer α f : Thermal expansion coefficient of the second layer

[0044] By the way, the value of E this time is 2.9GPa based on Polymer Research Series 42, 241-247 (1985), and ν s The value of was adopted as 0.4 based on Polymer Composites 17, No. 1 (1997). In addition, α s and α f was determined based on actual measurements under a nitrogen atmosphere.

[0045] The residual stress value obtained by calculating the formula (z) was 25 MPa, which was in good agreement with the residual stress value (24.1 MPa) obtained in Example 2. This means that the stress evaluation method of this embodiment can quantitatively obtain stress with good accuracy. Incidentally, the reason why the residual stress value obtained by calculating formula (z) closely matches the residual stress value obtained in Example 2 but not in Example 1 is presumably because the first and second layers in Example 2 are strongly bonded together, resulting in a state close to the model used when deriving formula (z).

Claims

1. a first step of irradiating an incident X-ray onto one surface of a laminated sample, the sample comprising a first layer containing a crystalline polymer and a second layer made of a resin material and provided in contact with one surface of the first layer, and detecting a diffracted X-ray emitted from the other surface of the sample; a second step of determining a microstrain ε of the lattice spacing of the crystal lattice of the crystalline polymer based on the diffracted X-rays; evaluating a stress σ between the first layer and the second layer based on the small strain ε.

2. The stress evaluation method according to claim 1, a third step of calculating a stress σ between the first layer and the second layer based on the minute strain ε, as well as the Poisson's ratio ν and the elastic modulus E of the first layer.

3. The stress evaluation method according to claim 2, the first layer comprises crystallites of two or more different orientations; In the first step, incident X-rays are incident on the microcrystals having the two or more different orientations, and as a result, when an angle between a surface of the first layer on which the second layer is provided and a lattice plane normal of the microcrystals included in the first layer is defined as ψ, two or more diffracted X-rays corresponding to two or more ψ are detected; In the second step, two or more microstrains ε are obtained based on the two or more diffracted X-rays, In the third step, a stress σ between the first layer and the second layer is calculated based on the two or more minute strains ε.

4. The stress evaluation method according to claim 3, In the first step, the two or more ψ are 1 , ..., ψ n (n is an integer of 2 or more), In the third step, the two or more microstrains ε are defined as 1 , ..., ε n (n is an integer of 2 or more) When I did, (sin 2 ψ 1 , ε 1 ),...,(sin 2 ψ n , ε n and calculating a stress σ between the first layer and the second layer by performing regression analysis on n data sets consisting of

5. The stress evaluation method according to claim 3 or 4, In the third step, the two or more small strains ε are plotted on the horizontal axis, and two or more different sin 2 A stress evaluation method in which ψ is plotted on the vertical axis, an approximation line is drawn, and the stress σ is calculated from the slope a of the approximation line based on the formula: a = (1 + v) σ / E.

6. The stress evaluation method according to claim 2, the first layer contains microcrystals such that, when an angle between a surface of the first layer on a side where the second layer is provided and a lattice plane normal of the microcrystals contained in the first layer is ψ=0°, In the first step, incident X-rays are incident on the microcrystals having ψ=0°, In the third step, a stress σ is calculated from the minute strain ε based on a formula: ε=-(ν / E)σ.

7. The stress evaluation method according to any one of claims 1 to 6, A stress evaluation method, wherein in the first step, the incident X-rays are incident non-perpendicularly to a surface of the first layer facing the second layer.

8. The stress evaluation method according to any one of claims 1 to 7, The stress evaluation method, wherein the incident X-rays are incident at an angle that is a Bragg angle with respect to a lattice plane of a crystal of a crystalline polymer contained in the first layer.

9. The stress evaluation method according to any one of claims 1 to 8, The stress evaluation method, wherein the incident X-rays are incident on the layered sample from a side of the second layer.

10. The stress evaluation method according to any one of claims 1 to 9, The stress evaluation method, wherein the second layer is composed of a cured product of a curable resin composition.

11. The stress evaluation method according to any one of claims 1 to 10, The stress evaluation method, wherein the second layer is composed of a cured product of an adhesive composition.

12. The stress evaluation method according to any one of claims 1 to 11, The stress evaluation method, wherein the first layer has a thickness of 0.5 mm or more.

13. The stress evaluation method according to any one of claims 1 to 12, A stress evaluation method, wherein the crystalline polymer contained in the first layer includes at least one selected from the group consisting of crystalline polyolefin, crystalline polyester, crystalline polyamide, crystalline polyether, crystalline polyurethane, crystalline polycarbonate, crystalline polyimide, crystalline polystyrene, and crystalline cellulose.

Citation Information

Patent Citations

  • Multilayer compensation film using material with specific glass transition temperature

    JP2008544317A

  • X-ray diffraction measurement device

    JP2017129514A

  • Thick steel plate and production method therefor

    JP2018031069A

  • Apparatus for x-ray measurement and slit plate used therefor

    JP2019086408A

  • X-ray stress measurement-purpose jig

    JP2019174212A